Effect of RGPP process on properties of Cr–Si–N coatings. (August 2014) - Zairi, A.; Nouveau, C.; Larbi, A. B. C.; Iost, A.; Martin, N.; Besnard, A.
<x content-type="archive" xml:space="preserve">Abstract</x> CrSiN films were deposited by reactive radio frequency magnetron sputtering in an Ar+N2 gas mixture. The nitrogen gas was injected in the deposition chamber using two methods: the classical constant injection and pulsed injection, the latter known as the reactive gas pulsing process (RGPP). Argon gas was continuously injected, whereas nitrogen gas was pulsed during the deposition. The RGPP was used to adjust the chemical composition and, consequently, allowed the improvement of the coating characteristics. The effect of process parameters such as silicon content and gas pulsing conditions (especially duty cycle α) on the crystallographic structure, chemical composition and morphology of the CrSiN layers is reported. It was found that the surface morphology evolves from a pyramid-like feature for 100% duty cycle to a typical cauliflower-like aspect, when duty cycle decreases to 84%. For shorter duty cycles, the growth produced a denser coating, with round and finer clusters.